Association of CD44+/CD24-cells to more aggressive molecular phenotypes in canine mammary carcinomas - Figueroa, Fernanda Carmello [UNESP]; Zanetti, Juliana da Silva; Ribeiro-Silva, Alfredo; Fonseca-Alves, Carlos Eduardo [UNESP]; Rocha, Noeme Sousa [UNESP] (Science Alert, 2015)
Leading the cause of death among female dogs, mammary gland tumor awakes the interest of the scientific community, mostly because the similarities in clinical presentation and evolution to breast cancer in women. Due to the importance of investigating canine mammary tumors, this research aims to identify the protein expression of CD44, CD24, MUC-1, CD10 and ESA by immuno-histochemistry. Thus, slides were prepared by the tissue microarray technique to assess the presence of these markers in different subtypes. Of the 112 tumors, 66.9% were positive for CD10 (75/112), 42.86% positive for CD24 (48/112), 21.43% for ESA (24/112), 20.54% for MUC-1 (23/112) and 5.35% for CD44 (6/112). Of these tumors, 3.57% showed the immuno-phenotype CD44+/CD24-(4/112). The results suggest that mammary gland tumors of female dogs were positives for stem cell markers, which may be associated with cancer stem cells. This association also may allow setting further models to study breast cancer in women.
Keywords: Canine; Mammary cancer; Stem cells; Tissue microarray